MEDIASI DALAM PENYELESAIAN SENGKETA MEDIK DOKTER DENGAN PASIEN (ANALISIS PUTUSAN PN NO. 38/PDT.G/2016/PN.BNA DAN PUTUSAN MAHKAH AGUNG NO. 1550 K/PDT/2016) - Nurul Ummah; Fifik Wiryani; Mokhammad Najih (Legality : Jurnal Ilmiah Hukum, 2019)
Mediation is a form of negotiation in an effort to resolve disputes both from parties who feel aggrieved by the related parties. Mediation is also able to produce a peace agreement from both parties so that it can provide benefits for both. Dispute resolution efforts can use several means of mediation, including through litigation and non-litigation, both of which have their own advantages and disadvantages. In the case in Banda Aceh, the legal route was prioritized compared to mediation because of the patient's dissatisfaction, as well as the case of cassation decisions that did not receive the compensation offered by the defendant so that the court route was taken. The mediation used did not have a positive impact on both parties so that the mediation was considered a failure. Mediating is expected to provide good and fair benefits to all disputing parties so as to produce a sense of satisfaction and justice without any shortcomings of both. This mediation is also regulated in 1999 Law number 30 concerning arbitrage and options for resolving disputes that are outside the court and according to the 2008 regulation number 1 regarding mediation in court which was later refined back to the Supreme Court regulation of the Republic of Indonesia No.1 of 2016. This research is a descriptive type of juridical normative research, with an approach to the law and secondary data obtained from various types of literature studies and document studies, then the data is analyzed qualitatively. With the result that the hope that the legislation has been perfected is that the dispute resolution process outside the court can be more optimal, and also that the community feels much better benefits and benefits from the existence of mediation.